Dignity as a Clue for the Future of Feminism - Ibarra, Diana (Feminist theology, 2026)
Feminism has had a rhizomatic evolution. However, a concept appears relatively often: dignity. We are aware of how problematic its foundation is, but conscious at the same time of its presence in important Women’s Human Rights documents. Our purpose is to present not only a historical overview of the uses of the term among the main exponents of feminism, but also to show its contemporary use. We endorse a Begriffsgeschichte (conceptual history) methodology to distinguish its uses and evolution. The concept of dignity has established points of agreement between the different feminisms. Therefore, talking about rights alone is not enough. In order to be respected, a common ground needs to be established. This value will help us build bridges and reach agreements among the different types of feminisms.